A Comparative Study of Gay and Lesbian Movement in Indonesia and America for the Struggle of Equality Recognition - Pawestri, Aprilina; Supanto, Supanto; Isharyanto, Isharyanto (Jurnal Cita Hukum, 2019)
Abstract:Studies of sexual orientation or sexual behavior in homosexual groups have been carried out from various aspects, such as religion, health, psychology, philosophy, anthropology, and law. This paper aims both on conducting studies of sexual orientation in gays and lesbians, and also in its movement. This study focuses on the comparison by discussing the history of the entry of gays and lesbians in America first. United State has made policy with the granting of same-sex marriage rights through the 2015 Obergefell Supreme Court ruling; hence, the rejection of same-sex marriage was unconstitutional action. Churches also dare to facilitate the process of same-sex marriage, by reason of following state decisions. The LGBT movement especially gays as a pioneer called the Gay Liberation Movement has a strong influence in America in fighting for equality, and has a big contribution to the granting of the right to same-sex marriage. This right is also supplemented by adoption rights. If this condition is compared to Indonesia which has lots of similar movement and becomes one of the biggest movements in Southeast Asia, in contrast, the majority of people reject the status. Meanwhile, gays and lesbians demand on the basis of human rights protection. Related to this condition, Indonesia has different views on human rights values. Human rights have universal principles, yet the actualization of human rights can be particular. Indonesia could be like America, if there are no regulations and restrictions on gay and lesbian individuals with differences in their sexual orientation, including the and lesbian movements.Keywords: Movement, Gay, Lesbian, United State, Equality Recognition Abstrak:Kajian tentang orientasi seksual ataupun perilaku seksual pada kelompok homoseksual telah banyak dilakukan dari berbagai aspek, baik aspek agama, kesehatan, psikologi, filsafat, antropologi ataupun hukum. Tulisan ini selain melakukan kajian tentang orientasi seksual pada gay dan lesbian, namun juga pada gerakan gay dan lesbian yang terorganisir. Kajian tentang gerakan gay dan lesbian ini menitikberatkan pada perbandingan dengan terlebih dahulu membahas tentang sejarah masuknya gay dan lesbian di Amerika. Amerika membuat kebijakan dengan dikabulkannya hak pernikahan sesama jenis melalui putusan Mahkamah Agung Obergefell tahun 2015, sehingga tindakan penolakan atas pernikahan sesama jenis merupakan perbuatan inkonstitusional. Gereja-gereja pun berani memfasilitasi proses pernikahan sesama jenis, dengan alasan mengikuti keputusan negara. Gerakan LGBT khususnya gay sebagai pelopor yaitu Gay Liberation Movement memiliki pengaruh yang kuat di Amerika dalam memperjuangkan kesetaraan dan memiliki andil besar atas dikabulkannya hak atas pernikahan sejenis. Hak ini dilengkapi pula dengan hak adopsi. Jika kondisi ini dibandingkan dengan Indonesia yang memiliki banyak gerakan serupa, bahkan menjadi salah satu gerakan terbesar di Asia Tenggara, namun mayoritas masyarakat menolaknya, sedangkan kaum gay dan lesbian menuntut atas dasar perlindungan Hak Asasi Manusia. Tentunya pada peristiwa yang sama Indonesia berbeda pandangan terhadap nilai-nilai HAM. HAM memiliki prinsip universal, namun aktulisasi HAM dapat menjadi partikular. Indonesia bisa menjadi seperti Amerika, jika tidak ada pengaturan dan pembatasan atas individu-individu gay dan lesbian dengan perbedaan orientasi seksual mereka, termasuk pada gerakan gay dan lesbian.Kata Kunci: Gerakan, Gay, Lesbian, Amerika, Pengakuan Kesetaraan Аннотация:Исследования сексуальных наклонностей или сексуального поведения в гомосексуальных группах проводились в различных аспектах, включая аспекты религии, здоровья, психологии, философии, антропологии или права. Данная статья не только проводит исследования сексуальных наклонностей геев и лесбиянок, а также их организованных движений. Данное исследование движений геев и лесбиянок фокусируется на сравнении, начиная с обсуждения истории появления геев и лесбиянок в Америке. Америка провела политику по предоставлению прав на однополые браки на основании решения Верховного суда Обергефелла 2015 года, поэтому отказ от однополых браков является неконституционным действием. Движение ЛГБТ, особенно гей-движение, как пионер Освободительного Движения Геев и Лесбиянок (GayLiberationMovement) оказывает сильное влияние в Америке на борьбу за равенство и играет большую роль в предоставлении прав на однополые браки. Если сравнивать это состояние с ситуацией в Индонезии, в которой есть много подобных движений, то большинство людей их отвергают, в то время как геи и лесбиянки требуют защиту на основе прав человека. Конечно, люди в Индонезии имеют разные идеи о ценностях прав человека. Индонезия может стать такой же страной, как США, если не будет распоряжений и ограничений перед личностям геев и лесбиянок с разными сексуальными наклонностями, включая движения геев и лесбиянок.Ключевые Слова: движения, гей, лесбиянкa, США, признание равенства